Longitudinal analysis of local government spending on adult social care and carers' subjective well-being in England. Issue 12 (23rd December 2021) - Zhang, Yanan; Bennett, Matthew R; Yeandle, Sue
Abstract : Objectives: Reform of England's social care system is repeatedly discussed in the context of increasing demand, rising costs and austere policies that have decreased service provision. This study investigates the association between unpaid carers' subjective well-being and local government spending on adult social care (ASC). Setting and participants: Our sample consists of 110 188 observations on 29 174 adults in England from the 2004–2007 British Household Panel Survey and the 2009–2018 UK Household Longitudinal Study. The data on local authorities' spending on ASC where participants live is derived from the publications Personal Social Care Expenditure and Unit Costs (2004–2016); and ASC Activity and Finance Report England (2016–2018). Outcome measures: Subjective well-being is measured by the 12-item version of the General Health Questionnaire (GHQ-12) and 12-item version of the Mental Component Summary (MCS-12). We applied fixed-effects linear models to investigate the moderating effect of ASC spending on the association between subjective well-being and caring, controlling for a range of socioeconomic and demographic variables. Results: Carers have a lower level of subjective well-being compared with non-carers, evident in their higher average GHQ-12 Likert score (β=2.7277 95% CI 0.2547 to 5.2008). Differences in the subjective well-being of carers and non-carers decrease with local government spending on ASC. Subjective well-being for carers was at a similar level to that of non-carers in high ASC spending local authorities (GHQ-12: −0.0123 95% CI −0.2185 to 0.1938, MCS-12: 0.0347 95% CI −0.3403 to 0.4098) and lower in other areas (GHQ-12: 0.1893 95% CI 0.0680 to 0.3107, MCS-12: −0.2906 95% CI –0.5107 to −0.0705). The moderating effect of ASC spending is found among people who care for 35+ hours per week. Conclusion: Government spending on ASC protects unpaid carers' well-being, and people providing more than 35 weekly hours of unpaid care are more likely to benefit from the current social care system.